2022
DOI: 10.3389/fimmu.2021.755890
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-Meditated Immunity Abnormalities Facilitate Hepatitis B Virus Co-Infection in People Living With HIV: A Review

Abstract: Hepatitis B virus (HBV) co-infection is fairly common in people living with HIV (PLWH) and affects millions of people worldwide. Identical transmission routes and HIV-induced immune suppression have been assumed to be the main factors contributing to this phenomenon. Moreover, convergent evidence has shown that people co-infected with HIV and HBV are more likely to have long-term serious medical problems, suffer more from liver-related diseases, and have higher mortality rates, compared to individuals infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 124 publications
0
6
0
1
Order By: Relevance
“…Возникающая в результате иммунного ответа системная воспалительная реакция связана с клиническим прогрессированием ВИЧ и возникновением сопутствующих заболеваний, не связанных с иммунодефицитом [21]. У пациентов, получающих АРТ, состав микробиома кишечника изменяется по сравнению с таковым у неинфицированных лиц, что предполагает влияние провоспалительного компонента со стороны бактериальной флоры желудочно-кишечного тракта независимо от эффективности АРТ и уровня вирусной нагрузки [22].…”
Section: бактериальная транслокация при вич-инфекцииunclassified
“…Возникающая в результате иммунного ответа системная воспалительная реакция связана с клиническим прогрессированием ВИЧ и возникновением сопутствующих заболеваний, не связанных с иммунодефицитом [21]. У пациентов, получающих АРТ, состав микробиома кишечника изменяется по сравнению с таковым у неинфицированных лиц, что предполагает влияние провоспалительного компонента со стороны бактериальной флоры желудочно-кишечного тракта независимо от эффективности АРТ и уровня вирусной нагрузки [22].…”
Section: бактериальная транслокация при вич-инфекцииunclassified
“…Analyses of gut bacteria in cross-sectional cohorts of HIV-infected and uninfected individuals have shown the changes in the bacterial microbiota of infected people. [26,27] Edda et al suggested that PLH had distinct gut microbiota. Generally, a decrease in commensal species and a gain in pathogenic taxa can be observed in PLH (Table 1).…”
Section: Gut Bacteriamentioning
confidence: 99%
“…[13,28] According to relevant research data, alterations of gut microbiota in PLH mainly manifest as changes in microbial diversity, a reduction in symbiotic beneficial bacteria, and an increase in potentially pathogenic bacteria. [26] However, due to the particularity of HIV, there are some differences in gut bacteria among different population structures (Table 1), which are mainly associated with the different sexual preferences, the duration and type of ART, and the status of immune response. [26] Also, some findings have indicated that maternal HIV status has a profound impact on the infant gut microbiota.…”
Section: Gut Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…An HIV-positive individual displaying an HIV-associated gut dysbiosis profile can, thus, readily develop HBV infection, as HIV-associated microbial translocation favors hepatocyte injury. Our group has recently published an extensive review discussing mechanisms whereby gastrointestinal microbiome dysbiosis and a "leaky" gut in PLWH increases susceptibility to HBV infection (132).…”
Section: Hiv-associated Gut Dysbiosismentioning
confidence: 99%